Multidisciplinary team management and cesarean delivery for a Jordanian woman infected with SARS-COV-2: A case report - Laila A. AlZaghal; Najwa AlZaghal; Safwan O. Alomari; Nail Obeidat; Basil Obeidat; Wail A. Hayajneh (Elsevier, 2020)
The SARS-COV-2 virus appears to have originated in Hubei Province in China towards the end of 2019 and has spread worldwide. Currently, there is little literature on COVID-19, and even less on its effect on pregnant mothers and infants. At this time, there are no clear recommendations specific to pregnant women with COVID-19. We report the multidisciplinary team management of a cesarean delivery for a woman infected with SARS-COV-2, including her pre-delivery care, intraoperative considerations, and post-delivery recommendations for the mother and baby. We also discuss the currently available recommendations and guidelines on the management of such cases.